Insights on Environmental Changes Where the World is Heading - Zielinski, Tymon; Pazdro, Ksenia; Dragan-Górska, Agata; Weydmann, Agata; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book presents valuable insights on a vast array of topics in the field of environmental studies. The works published in the book were presented within the scope of the 2013 Sopot Forum of Young Scientists. The Forum is an annual event which provides a platform for young researchers to present their work and exchange ideas with their peers. The aim of the forum is to make science more popular, so the speakers talked about their work in a way that was easily understandable. The book contains actual scientific papers on their own topics of interest. The papers represent different areas of environmental sciences, from biology to physics. The main umbrella topic for this book is "WHERE THE WORLD IS HEADING" and the papers are constructed in such a way as to try to answer this from each contributor's individual perspective.
The influence of matrix effects on trace analysis of pharmaceutical residues in aqueous environmental samples -- Valles marineris – a place full of answers -- Determination of tetracyclines residues in the Gulf of Gdańsk (southern Baltic Sea) sediments using a tandem solid-phase extraction with liquid chromatography coupled with tandem mass spectrometry -- A modern approach to aerosol studies over the Baltic Sea -- Water in the deepest crater of Mars -- Application of an object classification method for determining of the spatial distribution of sea bottom structures and their cover using images from a Side Scan Sonar.
Keywords: Climate change; Climate Change; Climate Change/Climate Change Impacts